2000
DOI: 10.1002/1097-4636(200102)54:2<241::aid-jbm11>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic study and syntheses of type I collagen and fibronectin of human periodontal ligament cells cultured on poly(ethylene-co-vinyl alcohol) (EVA) with collagen immobilization

Abstract: The purpose of this study was to regenerate the human periodontal ligament (PDL) around dental implants by using a hybrid structure of cells with materials, such as PDL cells + collagen + poly(ethylene-co-vinyl alcohol) (EVA) on titanium implant. Human PDL cells were cultured on the EVA surface coated with type I collagen and the cell adhesion and extension were investigated. Furthermore, collagen type I and fibronectin syntheses were analyzed. The serum free culture was also tried, to investigate the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…While it was found that the presence of collagen stimulated the cell cycle progression [37], long-term culture (8-10 days) showed a significant lower proliferation rate of osteoblasts, when compared with the noncoated titanium substrate [13,38]. On the other hand, a significant increase in the adhesion and proliferation rate of primary human periodontal ligament cells was found after type I collagen immobilization on poly(ethylene-co-vinyl alcohol) [39] which agrees with the results of our study. No references describing similar studies with human MSCs could be found in the literature.…”
Section: Article In Presssupporting
confidence: 91%
“…While it was found that the presence of collagen stimulated the cell cycle progression [37], long-term culture (8-10 days) showed a significant lower proliferation rate of osteoblasts, when compared with the noncoated titanium substrate [13,38]. On the other hand, a significant increase in the adhesion and proliferation rate of primary human periodontal ligament cells was found after type I collagen immobilization on poly(ethylene-co-vinyl alcohol) [39] which agrees with the results of our study. No references describing similar studies with human MSCs could be found in the literature.…”
Section: Article In Presssupporting
confidence: 91%
“…An interesting paper by Pham et al (2003), which discussed the ultimate protein-based coating that is a native extracellular matrix coating on Ti surfaces, closes this section. Briefly, osteoblast-like SAOS-2 cells were allowed to synthesize and assemble their extracellular matrix (ECM) on titanium surfaces.…”
Section: Morramentioning
confidence: 88%
“…Nanci et al (1998) also used Aminosilane chemistry, while Mikulec and Puleo (1996) and Puleo et al (2002) presented two interesting papers on the use of p-nitrophenylchloroformate chemistry to couple biomolecules to native hydroxyl groups and on amino functionalization by plasma deposition. Matsumura and co-workers presented an approach to the surface immobilization of collagen that was used also for the modification of Ti implants (Matsumara et al, 2000;Peng et al, 2001;Matsumara et al, 2002). Briefly, collagen was linked to poly(ethyleneco-vinyl alcohol) (EVA) coatings on Ti implants.…”
Section: Bmtis By Ecm Proteins Analytical Andmentioning
confidence: 99%
“…Implants in rabbit femurs showed a significant increase of bone growth and bone-implant contact in the case of collagen-immobilized surfaces. Alternatively, Matsumura et al 18) and Peng et al 19) designed a method of adhering polyethylene-co-vinyl alcohol (EVA) to titanium by a hot melt technique, and then immobilized collagen on titanium via the EVA film. However, these procedures are complicated and require several steps for immobilization of proteins on the titanium surface.…”
Section: Introductionmentioning
confidence: 99%